JEJARING PENDIDIKAN ISLAM; PROSES PEMBENTUKAN RELASI GURU DAN MURID PESANTREN DI KABUPATEN ACEH SINGKIL - Dahri, Dahri; Suyanta, Sri; Shadiqin, Sehat Ihsan; Ramli, Ramli (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
The role of the three Syekh Muda Waly students at the Darussalam Islamic Boarding School is crucial in the social and religious life of the community in Aceh Singkil Regency. They are Abu Bahauddin Tawar (1927-2008), Abu Zamzami Syam (1923-2013) and Abu Baihaqi (1931-2015). Interestingly, although the three have different educational characters, they studied at the Darussalam Islamic Boarding School led by Abu Syekh Muda Waly Al Khalidi (1961). Abu Sheikh Muda Al-Khalidi inherited religious knowledge such as fiqh monotheism of Sufism and the sanad of the Naqsabandiyah Khalidiah order. Through an actor-network theory (ANT) approach, this research attempts to map the process of forming student and teacher relationships between the three ulama and Syekh Muda Waly. The results of this research show. (1) The relationship between teacher and student is formed through scientific networks and tarekat sanad. (2) This relationship also impacts learning in the three Islamic boarding schools, which have the same curriculum structure and emphasize understanding fiqh, monotheism, Sufism, da'wah science, and tool science. (3) Such relations also make Darussalam the axis for scientific institutions in the three Islamic boarding schools. It is common for several students who have completed tsanawiyah or Aliyah education at the three Islamic boarding schools to continue to deepen their knowledge at the Darussalam Islamic Boarding School. This relationship shows the role of Abu Syekh Muda Waly Al-Khalidi and Islamic Boarding School Darussalam in building a scientific network within the social context of the Aceh Singkil community